2009
DOI: 10.1007/s10964-009-9488-7
|View full text |Cite
|
Sign up to set email alerts
|

Shared Agency with Parents for Educational Goals: Ethnic Differences and Implications for College Adjustment

Abstract: This study proposed and confirmed three ways in which college students can perceive shared agency and two ways in which they can perceive non-shared agency with parents when pursuing educational goals in college. Differences and similarities were examined among participants from four ethnic backgrounds (N = 515; 67% female): East Asian American, Southeast Asian American, Filipino/Pacific Islander American, and European American. Results indicated that Asian American youth reported higher levels of non-shared a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 29 publications
4
68
0
Order By: Relevance
“…Further communication with parents has its imprint on the adjustment of students (Agliata & Renk, 2008). Parents' educational goals differ by race impacting academic achievement (Chang et al, 2010). Thus the incidence of structural factors like leaving parental home as a transition to adulthood (A.…”
Section: Social Adaptationmentioning
confidence: 99%
“…Further communication with parents has its imprint on the adjustment of students (Agliata & Renk, 2008). Parents' educational goals differ by race impacting academic achievement (Chang et al, 2010). Thus the incidence of structural factors like leaving parental home as a transition to adulthood (A.…”
Section: Social Adaptationmentioning
confidence: 99%
“…Berg & Upchurch, 2007;Salmela-Aro & Little, 2007). This also applies to youths or emerging adults and their parents, who often work together on tasks and decisions during the transition to adulthood (Marshall et al, 2008;Young et al, 2008) and during educational transitions and challenges more specifically (Chang, Heckhausen, Greenberger, & Chen, 2010;Dietrich et al, 2011).…”
Section: Preferred Partners For Decision Making Advice Giving and Pmentioning
confidence: 99%
“…We explicitly focused on collaboration as the kind of involvement through which a PA should be most helpful to students choosing a major, because it reflects the most welcome, direct, and active role that another person may play (Berg & Upchurch, 2007). Collaboration or joint action has only started to receive research attention in real-life studies on career development and decision making (e.g., Chang et al, 2010;Marshall et al, 2008;Phillips et al, 2001;Schultheiss et al, 2001). We intended to show that considering work on collaboration that originated outside the career development area (cf.…”
Section: Introductionmentioning
confidence: 99%
“…In marital relationships, collaboration between partners has been found to maximize health and cognitive outcomes (Berg et al., ; Wiebe et al., ). However, when tested within an educational context among European and Asian American college students, perceived collaboration with parents in education was unrelated to academic outcomes (Chang et al., ). Consistent with current conclusions regarding the adaptability of parental autonomy support, it was found that parental support was positively related and parental directing of youth's education was negatively related to academic adjustment.…”
Section: Shared Agency With Parentsmentioning
confidence: 99%